Dilated intercellular space diameter as marker of reflux‐related mucosal injury in children with chronic cough and gastro‐oesophageal reflux disease. Issue 7 (11th February 2014) - Borrelli, O.; Mancini, V.; Thapar, N.; Ribolsi, M.; Emerenziani, S.; de'Angelis, G.; Bizzarri, B.; Lindley, K. J.; Cicala, M.
Summary Background The diagnostic corroboration of the relationship between gastro‐oesophageal reflux disease (GERD) and chronic cough remains challenging. Aims To compare oesophageal mucosal intercellular space diameter (ISD) in children with GERD, children with gastro‐oesophageal reflux (GER)‐related cough (GrC) and a control group, and to explore the relationship between baseline impedance levels and dilated ISD in children with GER‐related cough. Methods Forty children with GERD, 15 children with GrC and 12 controls prospectively underwent oesophagogastroduodenoscopy (EGD) with oesophageal biopsies taken 2–3 cm above squamocolumnar junction. ISD were quantified using transmission electron microscopy. Impedance‐pH monitoring with evaluation of baseline impedance in the most distal impedance channel was performed in both patient groups. Results A significant difference in mean ISD values was found between GrC patients (0.9 ± 0.2 μm) and controls (0.5 ± 0.2 μm, P < 0.001), whereas there was no difference between GrC and GERD group (1 ± 0.3 μm, NS). No difference was found in the mean ISD between GrC children with or without pathological oesophageal acid exposure time (1 ± 0.3 vs. 0.9 ± 0.2 μm), and there was no correlation between ISD and any reflux parameter. Finally, there was no correlation between ISD and distal baseline impedance values (r:−0.35; NS). Conclusions In children with reflux‐related cough, dilated intercellular space diameter appears to be an objective and useful marker of oesophageal mucosal injury regardless of acid exposure, and its evaluation should be considered for those patients where the diagnosis is uncertain. In children with reflux‐related cough, baseline impedance levels have no role in identifying reflux‐induced oesophageal mucosal ultrastructural changes.